PolÃtica de cotas para ingresso das pessoas com deficiÃncia nas universidades pÃblicas e sua consonÃncia com os preceitos da Carta Magna - Heloisa de Paula Pessoa Rocha (2011)
This study investigates the consonance between the system of quotes for the inclusion of the people with disabilities in the federal public universities and the Charta Magnum of 1988. The public polices have to obey to the elements of legitimation given by the public interest and others constitutional rules, since Brazil belongs to a democratic order. In fact, it is necessary to verify the conjecture of the political and juridical legitimation to confer the nature of positive discrimination to this kind of program.